Transrectal Ultrasound Guided Hydrodistension – A New Surgical Way in Transgender Surgery. Issue 6 (26th May 2021) - Panic, A.; Rahmani, N.; Kaspar, C.; Radtke, J.P.; Darr, C.; Henkel, A.; Hadaschik, B.; Tschirdewahn, S.; Hess, J.
ABSTRACT: Background: Creating the neovaginal canal in transwomen is one of the most delicate steps of Genital Gender Affirming Surgery (GGAS). Injury to the rectum is a rare but serious complication that can lead to further surgery and even creation of a colostomy. Aim: Implementation of a novel hydrospacing technique (HST) based on transrectal ultrasound (TRUS)-guided hydrodistension. Methods: Between June 2018 and June 2020 54 transwomen received GGAS with HST. Immediately before GGAS transperineal hydrodistension was performed using a TSK-Supra-Needle (20 Gauge, 120 mm length), that was placed under direct TRUS-guided visual control between Denonvilliers' fascia and the anterior rectal wall. 40 – 60 ml normal saline were administered perineally to separate Denonvilliers' fascia from the anterior rectal wall to create a dissection of at least 20 mm. For better intraoperative visualization the hydrodissected space was also dyed using 2ml of methylenblue while retracting the needle. A retrospectively analysed, clinically and demographically comparable series of 84 transwomen who underwent GGAS between June 2016 and June 2018 served as control group. All 138 surgeries were performed by the same experienced surgeon. Outcomes: The effect of the novel hydrospacing technique on neovaginal dimensions and operating time. RESULTS: Patients in both groups did not differ in baseline patient characteristics such as age and body mass index (HST 35 vs 38 years in control group, P = .44 and body mass index 26 vs 25 kg/m 2, P = .73). Vaginal depth and width were significantly larger in the HST subgroup as compared to controls (14.4 cm vs 13.5 cm, P = .01 and 4.2 cm vs 3.8 cm, P < .001). No statistically significant difference occurred in intraoperative rectal injury (n = 0 in HST group, n = 2 in control group, P = .26). Median total OR-time was comparable for GGAS including HST before vaginoplasty to standard technique (211 minutes for HST vs 218 minutes; P = 0.19). Clinical implications: The proposed additional surgical step during GGAS is minimally invasive and safe, simplifies GGAS and potentially helps to avoid complications such as rectal injury. Strength & Limitations: Single-surgeon series, limited follow-up time and no prospective randomization. CONCLUSION: HST is a safe and feasible procedure, which facilitates a safe preparation of the neovaginal canal during male to female GGAS.